Private Laws of the Territory of Kansas 137 (1860) - (:unkn) unknown (My University, 1860)
An Act to Amend and Consolidate the Several Act Relating to the City of Lawrence, § 35, pt. 7: Granted the city of Lawrence the authority to regulate the keeping and conveying of gun powder and other combustible and dangerous materials.
Keywords: GUNPOWDER - STORAGE